ANALISIS FAKTOR PENYEBAB KETIDAKDISIPLINAN SISWA DI SMA SANTUN UNTAN PONTIANAK - Utari, Nadya Dwi; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to find out the factors that lead to the indiscipline of students in SMA Santun Untan Pontianak. The research method used was descriptive research with a form of qualitative research. The data sources of this study were the headmaster, picket teacher, BK teacher, homeroom teacher, and some students of class XII IPS. In collecting the data, the researcher used direct observation techniques, direct communication techniques, and documentation. The tools of data collection used were interview, observation and documentation. In this study, researchers used the technique of examining data the level of trust (credibility) Perseverance monitoring and triangulation. The results of this study indicated the factors causing the indiscipline of students at SMA Santun Untan Pontianak are divided into internal and external factors. The internal factors that come from the students themselves were caused by family factors, disharmonious families, families who are busy working and families in distress are low while external factors were caused by school discipline that have not been applied by students and there was no firmness from the school for those who violate. Keyword: Analysis, Causes, indiscipline